Maternal Morbidity of Women Receiving Birth Center Care in New South Wales: A Matched‐Pair Analysis Using Linked Health Data. Issue 3 (17th June 2014) - Laws, Paula J.; Xu, Fenglian; Welsh, Alec; Tracy, Sally K.; Sullivan, Elizabeth A.
Abstract Background Around 2 percent of women who give birth in Australia each year do so in a birth center. New South Wales, Australia's largest state, accounts for almost half of these births. Previous studies have highlighted the need for better quality data on maternal morbidity and mortality, to fully evaluate the safety of birth center care. Aims This study aimed to examine maternal morbidity related to birth center care for women in New South Wales. Methods A retrospective cohort study with matched‐pairs was conducted using linked health data for New South Wales. Maternal outcomes were compared for women who intended to give birth in a birth center, matched with women who intended to give birth in the co‐located hospital labor ward. Results Rates of maternal outcomes, including postpartum hemorrhage, retained placenta, and postpartum infection, were significantly lower in the birth center group, after controlling for demographic and institutional factors. Interventions such as cesarean section and episiotomy were also significantly lower in these women, and the rate of breastfeeding at discharge was higher. There existed no difference in length of stay, admission to ICU, or maternal mortality. Conclusions Birth centers are a safe option for low‐risk women; however, further research is required for some rare maternal outcomes.